2014
DOI: 10.1007/s12020-014-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a monthly dose of calcidiol in improving vitamin D deficiency and secondary hyperparathyroidism in HIV-infected patients

Abstract: There are no data about the optimal supplementation therapy in HIV-infected patients with vitamin D (25OHD) deficiency. The aim of this study was to assess the effect of an oral monthly dose of 16,000 IU calcidiol. We performed a longitudinal cohort study of 365 HIV-infected patients (24 % females) was with sequential determinations of 25OHD, serum parathyroid hormone (PTH), calcium, and alkaline phosphatase. The efficacy and safety of supplementation in 123 patients were compared against dietary and sun expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…According to a recent review by Mansueto et al [ 96 ] the prevalence of vitamin D deficiency among HIV-infected individuals in both RLS and RRS varies widely across studies ranging from 25 to 93%, with an overall prevalence of 70.3 to 83.7%. Similarly, our review yielded high but similar prevalence of low vitamin D among HIV individuals regardless of ART use in both RLS [ 50 , 53 , 97 102 ] and RRS [ 61 , 103 109 ] with insufficient levels of up to 90% in Turkey [ 50 ] and the USA [ 103 ], Belgium [ 108 ], Spain [ 109 ] (Table 2 and Fig. 2 ).…”
Section: Introductionsupporting
confidence: 56%
“…According to a recent review by Mansueto et al [ 96 ] the prevalence of vitamin D deficiency among HIV-infected individuals in both RLS and RRS varies widely across studies ranging from 25 to 93%, with an overall prevalence of 70.3 to 83.7%. Similarly, our review yielded high but similar prevalence of low vitamin D among HIV individuals regardless of ART use in both RLS [ 50 , 53 , 97 102 ] and RRS [ 61 , 103 109 ] with insufficient levels of up to 90% in Turkey [ 50 ] and the USA [ 103 ], Belgium [ 108 ], Spain [ 109 ] (Table 2 and Fig. 2 ).…”
Section: Introductionsupporting
confidence: 56%
“…Other ART-initiation and switch studies have shown similar results [37, 6163], suggesting that perhaps higher repletion doses in HIV-subjects on EFV compared to those not on EFV are necessary. However, the supplementation studies that have evaluated changes in 25(OH)D or percentage of subjects reaching optimal 25(OH)D concentrations in ART-stable subjects have not shown any differences between those on or not on EFV [44, 46, 57]. Our current findings support this idea that once an individual is stable on an EFV-based regimen, no difference in repletion doses are necessary.…”
Section: Discussionsupporting
confidence: 75%
“…Serum 25(OH)D increased slightly in the supplemented patients, and declined in those not given a supplement. Other studies among HIV patients have also shown an increase in serum 25(OH)D with vitamin D supplementation (12,13,32,33) . Longitudinal studies in HIV patients without vitamin D supplementation (34,35) have reported a decrease in serum 25(OH)D with ART initiation as observed in our study.…”
Section: Discussionmentioning
confidence: 84%